An exploration of the consistency limits of the analytical hierarchy process and its impact on contractor selection. Issue 1 (2nd January 2018) - Martin, Hector; Koylass, Joey; Welch, Ferida
ABSTRACT: As project failure risk is reduced with the inclusion of additional factors when choosing a contractor, so too is client risk. As an approach to multi-criteria decision-making, the analytical hierarchy process (AHP) is explored to determine whether the traditional AHP (consistency ratio 0.1) and the weakly consistent AHP (consistency ratio 0.5–0.1), currently used for contractor selection, produce the same result. A case study comparing both methods reveals that the top-ranked contractor was the same while the ranking of the remaining contractors were different. Because choosing the right contractor can mean the difference between project success and failure, the consistency rule for the traditional AHP should be used for contractor selection, and not the weakly consistent AHP, especially as inconsistency increases random outcomes. This finding becomes important if the first-choice contractor opts out of a contract or is terminated by the client and a suitable second choice must be made from the original bids.